"Are the new proposals for reform of directors' disqualification requirements in the UK sufficient or cosmetic?". Issue 4 (11th July 2016) - Mugarura, Norman
Abstract : Purpose: The paper aims to examine the circumstances in which directors who fail to perform their duties and responsibilities with due diligence can be sanctioned and to evaluate whether the recent changes for reform both in the UK and European Union (EU) are adequate to deter directors from misfeasance or to cure defects in the law. The purpose of this paper is to articulate regulatory regimes for disqualification of corporate directors and the proposed changes to tighten loose ends in this area of commercial law. This paper articulates the duties and responsibilities of Corporate Officer and the varied context in which they are manifested in the UK. Owing to the onerous nature of corporate directorship, directors cannot passively sit in boardrooms or on their committees, but they need to demonstrate that they are hands on to get things done as expected. The first part of the paper articulates the current regimes on director's disqualification so that it is used as a basis to examine the efficacy of the proposed changes for reform both on this area in the UK and Europe. The second part of the paper examines the proposed reform for change both in UK and in Europe and their efficacy to plug in law and practice. This area of corporate law is increasingly regulated by a number of agencies to ensure that directors perform their duties and responsibilities with due diligence. Design/methodology/approach: The paper is structured in two parts whereby the first part examines the framework for disqualification of corporate directors and related issues in the UK. The second part articulates recent changes in the law on director's disqualification with a view to evaluate whether these changes are robust enough to enhance the position of shareholders to ensure the company is well-managed for their interests or whether overregulation is inimical to the company by hindering directors from executing their corporate responsibilities with a measure of discretion. Findings: The findings reflect that regulatory reforms should be evolved and implemented to strike a balance in ensuring that regulatory regimes are implemented not to penalise corporate directors unnecessarily but also to ensure that rules are respected. The paper urges caution because overregulation can inhibit corporate director from taking necessary risks (to be more guarded) to secure their positions. Research limitations/implications: The paper was written on the basis of secondary and primary data sources often also alluding to empirical cases studies. It would have been better to carry out structured interviews to corroborate some of the findings of the paper. Practical implications: Corporate governance is an onerous task, and thus, it requires corporate officers to exercise due diligence in execution of their duties and responsibilities. Getting the issue of corporate governance wrong often has ramifications for the company and respective corporate officers. These ramifications include not least penalising individual directors by disqualification from holding corporate directorship or the company being wound up altogether. Social implications: Corporation plays an important role in the society such as creating employment opportunities, markets for goods and services, generating revenues to governments and the list goes on. Therefore, the way they are managed has important implications for societies and governments. Originality/value: Even though the paper was written on the basis of primary and secondary data sources, it was done in a distinctive manner to foster the objective for writing it.